Sedentary Behaviour A Contemporary View - Marques, Adilson; Rúbio Gouveia, Élvio (IntechOpen, 2021)
Nowadays, the increasing availability of technology and the transition towards more sedentary occupations and recreation activities make sedentary behaviours an emerging research topic in behavioural epidemiology. This is particularly important because the available evidence consolidates the harmful relationship between sedentary behaviour and cardiometabolic risk markers and health outcomes. While the feasibility and benefits of changing sedentary behaviours have been demonstrated, this knowledge underpins the need for intersectoral public health interventions in workplaces and school settings. This book examines sedentary behaviours, current methods of assessment, the risk these behaviours present to individual health, and the importance of their interruption.